Vaping cannabis among adolescents: prevalence and associations with tobacco use from a cross-sectional study in the USA. Issue 6 (13th June 2019) - Kowitt, Sarah D; Osman, Amira; Meernik, Clare; Zarkin, Gary A; Ranney, Leah M; Martin, Jim; Heck, Courtney; Goldstein, Adam O
Abstract : Objective: Previous research suggests that some adolescents are using e-cigarette devices to vaporise ('vaping') cannabis in the form of hash oil, tetrahydrocannabinol (THC) wax or oil, or dried cannabis buds or leaves. However, it is unclear how adolescents who vape cannabis use other tobacco products. This study examined the extent to which adolescents reported ever vaping cannabis and investigated how demographic variables and tobacco behaviours were associated with use. Design: We used cross-sectional data from adolescents (total response rate 64.5%) who participated in the 2017 North Carolina Youth Tobacco Survey. SAS logistic regression survey procedures were used to account for the complex survey design and sampling weights. Setting: North Carolina, USA. Participants: Adolescents in high school (n=2835). Primary outcome and measure: Adolescents were asked to indicate whether they had ever used an e-cigarette device with marijuana, THC or hash oil, or THC wax. Results: Approximately 1 in 10 high school students reported ever vaping cannabis in the overall sample (9.6%). In multivariable models, adolescents who reported using cigars (adjusted OR (aOR) 3.76, 95% CI 2.33 to 6.07), waterpipe (aOR 2.32, 95% CI 1.37 to 3.93) or e-cigarettes (aOR 3.18, 95% CI 2.38 to 4.25) in the past 30 days had higher odds of reporting ever vaping cannabis compared with their counterparts. There was no significant association between use of smokeless tobacco (aOR 0.89, 95% CI 0.42 to 1.91) or use of cigarettes (aOR 1.27, 95% CI 0.71 to 2.29) in the past 30 days and odds of reporting ever vaping cannabis. Conclusions: These findings provide evidence that large numbers of high school students who use tobacco products have vaped cannabis. As tobacco control policies—such as communication campaigns or smoke-free laws—increasingly focus on e-cigarettes, attention to understanding how adolescents use e-cigarettes to vape substances other than nicotine is essential.